Temporal Patterns of Arctic and Subarctic Zooplankton Community Composition in Jones Sound, Canadian Arctic Archipelago (1961–62, 1963) - Apollonio, Spencer (ARCTIC, 2013)
An analysis of overwinter (1961–62) and early summer (1963) collections of zooplankton in Jones Sound, Canadian Arctic Archipelago, found 31 life forms and species, of which 11 species of copepods were dominant. The collections are the earliest on record from the archipelago. These 50-year-old data form a historical base that may assist in analyzing impacts of changing patterns of sea ice distributions. Water-mass-diagnostic copepod species in this study varied with the seasons; those with boreal Atlantic-Subarctic water affinities were present in the winter, but absent or few in number in the summer. Those with Arctic Basin water affinities were few or absent in winter but present or found in greater numbers in the summer. These variations in copepod species may be related to varying presence or proportions of boreal Atlantic water or Arctic Basin water in Jones Sound as also suggested by concurrent physical and chemical oceanographic data. The copepod species found in Jones Sound are also present or dominant in comparable Arctic waters from East Greenland to the Beaufort Sea and in the Arctic Basin, as reported elsewhere, and all reports differ significantly in the relative numbers of the species present from season to season or year to year. Such differences within Jones Sound are documented between the data reported here and those from the summer of 1980 reported elsewhere. It is suggested that these variations also reflect the differing presence or proportions of boreal Atlantic and Arctic Basin water. The conclusion is that Jones Sound and other High Arctic waters are subject to the presence or absence of Arctic Basin waters and boreal Atlantic waters and that the composition of the copepod communities is indicative of those changes. L’analyse d’ensembles de zooplancton prélevés au cours d’un hiver (1961-1962) et au début d’un été (1963) dans le détroit de Jones, archipel arctique canadien, a permis de repérer 31 espèces et formes de vie, dominées par 11 espèces de copépodes. Ces ensembles sont les plus ...